The Factors of Adolescents to Use Vape at Samarinda in 2021 - Eri Ramadhan; Rosdiana; Sumadi (Universitas Widya Gama Mahakam Samarinda, 2022)
Background: Cigarettes have a vape or electrical cigarette which used in conventional, its ingredients without tobacco but a liquid that is heated and evaporated in various flavors as develop innovation. Indonesia has increase the using vape of adolescent from the tobacco smokers or the vape smokers itself. Objectives: The purpose of this research is analysis of the character, knowledge, and causes of adolescent use vape. Research Metodes: The method of this study is qualitative with a study approach. The subjects are 5 adolescents which used vape and determined by technic of collecting data Snowball Sampling with interview guidelines as instruments. Results: The results of this study showed that adolescent knew and used a vape since 8 to 18 years. They are courier, two students, freelance, and college student. Adolescent knowledge related to vape or e-cigarettes is good and has no effect on the attitude of using e-cigarettes because although adolescents know the dangers of vaping but still use the vape. The Environmental factors such as the influence of friends, the influence of family, and easily to use vape become factors of teenagers using vape, lifestyle factors such as looking impressive when using vape and following the trend into factors of teenagers using vape, then the factor of exposure to the internet through social media becomes a factor of teenagers to use vape. Conclusion: Based on the study is the adolescent under 18 years old should not use the vape. However, the user of the vape is over the 18 years old or do not use at all.